Behaviour of concrete-encased CFST stub columns subjected to long-term sustained loading. (December 2018) - Ma, Dan-Yang; Han, Lin-Hai; Li, Wei; Hou, Chao; Mu, Ting-Min
Abstract: Concrete-encasedconcrete-filled steel tube (CFST) column consists of a CFST component and an outer reinforced concrete (RC) encasement. This paper numerically investigates the behaviour of concrete-encased CFST columns subjected to long-term sustained loading. A finite element analysis (FEA) model is established which incorporates the time-dependent behaviour of concrete under sustained loading using the viscoelastic model. The FEA model is validated against the experimental results from long-term loading tests. By using the FEA model, the behaviour of concrete-encased CFST columns subjected to long-term loading is thoroughly analysed, such as the full-range strain development, the internal force distribution among different components, the confinement effects between the steel tube and surrounding concrete, and the comparisons of three types of columns, i.e. concrete-encased CFST column, RC column and traditional CFST column. The creep deformation of the concrete-encased CFST column is also evaluated by the FEA model and existing design standards. The parametric analysis is conducted to investigate the influence of various parameters on the strength degradation of concrete-encased CFST columns, including the material strength, the steel ratio of CFST component, the sectional configuration, longitudinal rebar ratio, stirrup characteristic value, and the long-term axial load level. Finally, the ultimate strength of the concrete-encased CFST columns after long-term loading is evaluated, with calculation tables provided for the referencing of practical design. Highlights: A FEA model is developed to represent the long-term behaviour of concrete-encased CFST column. The full-rangeload-strain-age relationship of the composite column is investigated. Parametric analysis is presented to investigate the influence of various parameters.